2015
DOI: 10.15192/pscp.sa.2015.10.1.4954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some commercial bacterial biofertilizers and isolates against root knot nematode, Meloidogyne incognita infesting green bean, Phaseolus vulgaris

Abstract: Under field conditions, Four commercial biofertilizers namely, phosphorine (containing phosphate dissolving bacterium namely Bacillus megatherium or megaterium), Rhizobacterin (containing plant growth promotimg bacteria e.g. Bacillus spp. and Pseudomonas fluorescens), potassiumag ( containing potassium dissolving bacterium namely, Bacillus circulans), al-aukadin (containing Rhizobium phaseoli) as well as bacteria, Pseudomonas fluorescens and Serratia spp. as liquid cultures either alone or in combination were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In recent years, studies have shown the importance of natural nematicidal compounds in the plants themselves that have potential to suppress nematode populations (Pavaraj et al, 2010;Moosavi, 2012;Nelaballe and Mukkara, 2013;Muniasamy et al, 2010). Many botanical extracts have been found to contain phytochemicals such as alkaloids, tannins, saponins, flavonoids, diterpenes, glucosinolates, acetylenes and thinlys (Chitwood, 2002) which are effective against plant parasitic nematodes ( Goswani and Vijayalakshmi, 1986;Adegbite, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have shown the importance of natural nematicidal compounds in the plants themselves that have potential to suppress nematode populations (Pavaraj et al, 2010;Moosavi, 2012;Nelaballe and Mukkara, 2013;Muniasamy et al, 2010). Many botanical extracts have been found to contain phytochemicals such as alkaloids, tannins, saponins, flavonoids, diterpenes, glucosinolates, acetylenes and thinlys (Chitwood, 2002) which are effective against plant parasitic nematodes ( Goswani and Vijayalakshmi, 1986;Adegbite, 2003).…”
Section: Introductionmentioning
confidence: 99%